The Use of Laser Treatment in Combination with Fenofibrate for the Prevention of Diabetic Retinopathy - D. Z. Jalalova; L. Yarasheva (American Journal of Bioscience and Clinical Integrity, 2025)
The primary method of preventing blindness due to diabetes remains retinal laser coagulation. Following the completion of large multicenter studies such as DRS and ETDRS in the early 1990s (which are still considered classic), the main indications and types of laser interventions were established [1,2,3,4]. In the years that followed, the laser treatment techniques proposed by these studies have undergone minimal changes. Most of the work in this field has focused on modifying the DRS-ETDRS methods to reduce various side effects of laser treatment. With the advent of intravitreal injections of crystalline corticosteroids and vascular endothelial growth factor inhibitors, these have been combined with different types of laser interventions. While intravitreal injections of corticosteroids or anti-angiogenic agents did not meet expectations in terms of isolated therapy, they are now actively used as part of combined treatment with laser coagulation, which has proven to be significantly more effective.